Notes on the problem of temporality by Ernesto De Martino - Guerbo, Maririta (Scenari, 2022)
The article presents an examination of theoretical proposals on the theme of temporality put forward by the anthropologist Ernesto De Martino. In a progression from the individual to the collective to the historical level, in which mediations still remain problematic, De Martino elaborates an active and plastic conception of temporalisation. Time, understood as an a priori form of sensibility, can be shattered and thus interrupted. Reality itself is subject to changes that make it appear less like a natural term than a cultural term. For its part, the ritual institution fixes the shattered form and allows man to make time pass beyond the traumatic event that interrupted it. My aim is to show the fruitfulness of De Martino’s conceptual hybridisation, in a close comparison between ethnographic material and some classical sites of philosophy, such as Kant’s transcendental and phenomenology.